A Study on Antibiotic Sensitivity Pattern in Children Hospitalized for Urinary Tract Infection in a Tertiary Care Hospital in South India - Shaji, Shintu; Vinayakumar, Syamaprasad Thachethukunnil; Shaji, Shilpa (Journal of Pharmacy Practice and Community Medicine)
Background: The etiology of urinary tract infection (UTI) and their antibiotic sensitivity pattern vary from time to time and across different areas in India. This study is designed to analyse the resistance of uropathogens to commonly used antibiotics. Aim: To study antibiotic resistance trends of uropathogens and assess the antimicrobial utilization pattern according to the antimicrobial susceptibility test in the paediatric department of a tertiary care hospital. Materials and Methods: It was an ambispective observational cohort study conducted in 144 patients admitted with UTI for a period of one year and observed for recurrent UTI for the next one year. Results: E. coli (50%) was found to be the most common cause of UTI followed by Klebsiella (22.22%). E. coli and other isolates were more sensitive to Meropenem and Amikacin compared to other antibiotics tested. These isolates show increasing resistance to commonly used antibiotics. Most (74.31%) children were given single antimicrobial agent. Majority of the children were prescribed with Cephalosporins (60.41%), followed by Penicillin derivatives (29.17%) and Carbapenems (11.11%). Out of 144 children, antibiotics were prescribed according to culture sensitivity report in only 31.94%. Among children whose antibiotics were not selected based on the culture report, 40 had recurrent UTI in the following year. Conclusion: Recurrent UTI can occur if adequate antimicrobial therapy based on antimicrobial susceptibility test is not administered during the initial UTI episode. Close cooperation between physicians, microbiologists and pharmacists is essential to ensure that UTI patients receive antimicrobial therapy, if required based on local susceptibility data.
Keywords: UTI; Uropathogens; Antimicrobials; Pediatrics; Antibiotic resistance.